Hemodialysis Vascular access Construction in the Upper Extremity: A Review. Issue 2 (March 2015) - Lew, Susie Q.; Nguyen, Bao-Ngoc; Ing, Todd S.
Purpose: This article reviews the conventional vascular access types in the upper extremities for hemodialysis. Methods: We performed a literature search for autogenous arteriovenous fistula in the upper extremities. Results: The upper extremities have four potential sites: radio-cephalic or radio-basilic transposition in the forearm, and brachio-cephalic or brachio-basilic transposition in the upper arm. A pre-operative Duplex ultrasound provides valuable information regarding arterial inflow and venous outflow. The surgical approach to fistula formation and final product depends on vein diameter and length as well as proximal vein patency. The discussion focuses on access outcomes and management of common complications. Conclusions: The upper extremity arteriovenous fistula is the preferred access for hemodialysis. A number of arteriovenous fistulas can be created in the upper extremities. The Duplex ultrasound identifies suitable arteries and veins for successful arteriovenous hemodialysis fistula creation. Arteriovenous hemodialysis fistula has the best long-term patency outcomes and the lowest associated morbidity and mortality. Early detection and intervention can save the fistula when complications occur.